Frequency of Hyperbilirubinemia in Perforated Appendicitis - A Current Update on Diagnostics and Management. - Muhammad Khalid, M. Zeeshan Sikandar, Sardar Z. Akbar Khan, Warda Khalid, Hafiz Muhammad Abdullah Tahir, Tayyaba Tahir, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Perforated appendix can be detected earlier by chemically with the aid of hyperbilirubinemia. It is a simple non-invasive modality that can aid to detecting complicated appendicitis and avoid morbidity. Aim: To assess frequency of hyperbilirubinemia in patients undergoing appendectomy due to perforated appendicitis. Methods: A descriptive cross-sectional study was conducted in which a total of 75 patients undergoing emergency appendectomy due to perforated appendicitis and age 15-70 years were recruited. Patients with CLD, pregnancy, Congenital or acquired biliary disease, alcoholism and hemolytic disease were excluded. Blood sample was obtained and was sent to the hospital histopathology laboratory and it was reported by consultant pathologist for assessment of hyperbilirubinemia. Results: Age range in this study was from 15-70 years with mean age of 30.69±14.37 years. Majority of the patients 56(74.67%) were 15-40 years of age. Out of these 75 patients, 43(57.33%) were male and 32(42.67%) were females. Mean hyperbilirubinemia was 1.67±0.87 mg/dl. Frequency of hyperbilirubinemia in patients undergoing appendectomy due to perforated appendicitis was found in 63 (84.0%) patients. Practical implication: This will aid in prompt diagnosis and early management of perforated appendix, and serum bilirubin can be used as modality for diagnosis in the absence of ultrasound facility. Conclusion: Frequency of hyperbilirubinemia in patients undergoing appendectomy due to perforated appendicitis is very high. Keywords: perforated appendicitis, hyperbilirubinemia, appendectomy, bilirubin level, perforation, sensitivity.